2021
DOI: 10.1186/s13018-021-02283-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic effects on orthopaedic surgeons in British Columbia

Abstract: Background COVID-19 was declared a global emergency in the first quarter of 2020. It is has resulted in and continues in over a million deaths worldwide and halted medical systems and particularly elective surgeries worldwide. The aim of this study was to identify the effect of the initial COVID-19 pandemic months on orthopaedic surgeons in British Columbia. Methods The study surveyed (June until August 2020) 187 orthopaedic surgeons in British Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…On average, practitioners reported 60% decrease in patient volume and 55% decrease in revenue since the beginning of the pandemic. A decrease of overall acute trauma referral rates during the COVID-19 outbreak was also reported in several other regions along the globe [28][29][30] . In most Latin America countries, where lockdown was imposed in March, 91.8% of respondents in our study reported being concerned about their financial health, with 62.7% of them having their largest source of income from private practice.…”
Section: Discussionmentioning
confidence: 53%
“…On average, practitioners reported 60% decrease in patient volume and 55% decrease in revenue since the beginning of the pandemic. A decrease of overall acute trauma referral rates during the COVID-19 outbreak was also reported in several other regions along the globe [28][29][30] . In most Latin America countries, where lockdown was imposed in March, 91.8% of respondents in our study reported being concerned about their financial health, with 62.7% of them having their largest source of income from private practice.…”
Section: Discussionmentioning
confidence: 53%
“…Fifty-nine articles met the inclusion criteria and were considered for the analysis. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 The excluded thirty-four papers were editorials, letters, duplicate entries, and articles with no discussion on telemedicine even in the full text ( Figure 1 ). The monthly contributions trend of the orthopaedic telemedicine-related articles is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Most surveys reported widespread adoption of telemedicine as the main patient care modality. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Telemedicine can address the general and specialised needs of osteoporotic patients, paediatric deformities, fracture patients, and sports injuries. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 High patient and doctor satisfaction has been recorded with telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some procedures that were initially scheduled for the April-September 2020 period may have been rescheduled to October 2020 or later and thus not included in this analysis. Pandemic-related delays in access to preventive care, specialist consultations and presurgical testing and imaging also added to the backlog of surgeries created by cancellations during the first wave of the pandemic (CMA 2021;Duong 2021;Laing and Johnston 2021;Simon and Regan 2021).…”
Section: Discussionmentioning
confidence: 99%